Corporate governance structure and bank performance in Iraq - Abdullah, Abdullah Saeed (2019)
This study examines corporate governance practices in Iraq by the bank industry. Weak corporate governance has caused to the poor performance of listed firms in Iraq. Hence, the current research aims to examine the relationship between corporate governance structure and Iraqi banking performance. Bank performance is measured through return on assets (ROA) as the dependent variable. The corporate governance structure, however, is measured through the board of director’s characteristics (board of director’s size, gender diversity, board of directors meeting) as the independent variables. This research used secondary data from the annual report of sixteen banks listed in the Iraq stock exchange for the year of 2014-2017 with 64 bank-year observations. Agency theory is used as the underpinning theory to support the model of this study. For data analysis, panel data analysis is employed with both descriptive and correlation analysis through linear regression to investigate the corporate governance structure and bank performance. The empirical result demonstrates that the relationship between board size and ROA is negatively significant. The relationship between gender diversity and ROA is also found negatively significant as illustrated from the previous relationship. This study also found that the association between board meeting and ROA is negatively insignificant.